PENEGAKAN HUKUM TINDAK PIDANA KEHUTANAN DI WILAYAH HUKUM KEPOLISIAN RESOR INDRAGIRI HULU BERDASARKAN UNDANG-UNDANG NOMOR 41 TAHUN 1999 TENTANG KEHUTANAN - Giovani Barutu, Andi Matias; Yophie, Syaifullah; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Forest of state asset which is very worth, which its existence ought to under the aegis of state, pursuant to matter of hence government release regulation Number 41 Year 1999 about Forestry and of other regulation to protecting it. But in reality of straightening of law of the regulation not walk better because many resistanceThis type research can be classified in type research of empirical yuridis. Research of empirical yuridis is form or infusion of real penal research result or according to fact which is life in peopole. This research is conducted by in Police of Resor Indragiri Hulu. while and population of sample to represent the overall of side related to problem of accurate in this research. Source of used data, primary data, data of sekunder, and data of tertier. Technique data collecting in this research with interview, library study, and obsrvasi later then with analysing and process data qualitative and yield data of deskriktif later then take conclusion inductively.From result of research there is how much matter able to be concluded among others is the straightening of forestry doing an injustice law by Police of Resor Indragiri Hulu which not yet walked better because regional broadness of Sub-Province of Indragiri Hulu, limitation of government officer, peratuan pursuing investigation process, the increasing of modus of opradi, its minim of facilities and basic facilities, culture of society, existence of government officer oknum protecting perpetrator of forestry doing an injustice. As for conducted effort that is, for example is first, performing a special education to investigator, second, co-ordinate with Police of Forestry, third, doing of razia